Overlapping Claim On EEZ In The Northern Area Of The Malacca Straits Between Indonesia And Malaysia : The Implications Of Unresolved Dispute - Angkasari, Wildani; Abdullah, Kamarulnizam; Abdul Rohim, Asmar; Ahmad, Mohammad Zaki (2017)
Objective:This paper examines the negotiation issues and implications arising from unresolved overlapping EEZ claims in the northern region of the Malacca Straits between Indonesia and Malaysia.It will particularly focus on the impacts of this unresolved dispute to their bilateral relations, law enforcement, and management of marine resources. Methodology:The analysis framework of this paper is premised on desktop analysis. This qualitative approach identifies, collects, and assesses both primary and secondary data obtained from a wide range of published and unpublished materials, including internet resources.The main data collection technique is through structured interview and library research. Primary data are sources from international treaty instruments, legislation's, and court cases, while sources of secondary data are generated from journal articles, books, book chapters, and newspaper cuttings.Results: The failure of Indonesia and Malaysia to agree on EEZ boundary limits for both countries in the northern region of the Malacca Straits has led uncertainty over their jurisdictional status, as well as raising a number of enforcement related issues and affecting their bilateral relations.This paper reveals that Indonesia and Malaysia have made little progress in resolving their dispute over overlapping EEZ claims in the Straits, albeit there have been numerous diplomatic negotiation and dialogue sessions between the two governments. This failure has arguably created management and enforcement difficulty to the relevant government agencies in the disputed areas, while at the same time not only caused friction and conflict in Indonesia-Malaysia relations but also animosity among local fishing communities across the straits